2016
DOI: 10.1152/ajprenal.00594.2015
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-6 inhibition attenuates hypertension and associated renal damage in Dahl salt-sensitive rats

Abstract: Immune cells in the kidney are implicated in the development of hypertension and renal damage in the Dahl salt-sensitive (SS) rat. Interestingly, interleukin 6 (IL-6) mRNA is 54-fold higher in T-lymphocytes isolated from the kidney compared with circulating T-lymphocytes. The present experiments assessed the role of IL-6 in the development of SS hypertension by treating rats (n = 13-14/group) with an IL-6 neutralizing antibody or normal IgG during an 11-day period of high-salt (4.0% NaCl chow) intake. The mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(52 citation statements)
references
References 45 publications
(61 reference statements)
0
50
0
2
Order By: Relevance
“…Previous studies using animal models of hypertension have shown that IL-6 may have a role in pathogenesis of hypertension [43,44]. Furthermore, inhibition of IL-6 was connected to attenuation of associated renal damage [45][46][47]. Thus, we believe that antihypertensive effect of linagliptin may be derived from reversing IL-6 upregulation in doxorubicin nephropathy.…”
Section: Discussionmentioning
confidence: 73%
“…Previous studies using animal models of hypertension have shown that IL-6 may have a role in pathogenesis of hypertension [43,44]. Furthermore, inhibition of IL-6 was connected to attenuation of associated renal damage [45][46][47]. Thus, we believe that antihypertensive effect of linagliptin may be derived from reversing IL-6 upregulation in doxorubicin nephropathy.…”
Section: Discussionmentioning
confidence: 73%
“…IL-6 is a proinflammatory cytokine produced by various cells including macrophages, T-lymphocytes, endothelial cells, and vascular smooth muscle cells 35 . Chronic treatment of anti-IL-6 antibody reduced salt-sensitivity and renal macrophage accumulation in SS rats 3 . Rapamycin inhibition of IL-6 expression could therefore also account for some of the anti-inflammatory effects of rapamycin 36 .…”
Section: Discussionmentioning
confidence: 94%
“…Renal inflammation is a common feature of experimental and clinical hypertension, with lymphocytes and macrophages localizing to regions of renal injury 2, 3 . In the commonly used Dahl salt-sensitive (SS) rat, it has been shown that renal inflammation amplifies the hypertension and renal damage 4, 5 , similar to observations obtained from hypertensive patients 1, 6 .…”
Section: Introductionmentioning
confidence: 99%
“…IL-1β is closely associated with renal inflammation [48]. IL-6 has also been shown to participate in the salt-sensitive hypertension and renal injury in Dahl S rats [49]. Our results showed that high salt intake significantly increased the mRNA levels of pro-inflammatory factors IL-1β and IL-6 and that VA blocked high salt-induced increases in pro-inflammatory factors in the renal medulla in Dahl S rats.…”
Section: Discussionmentioning
confidence: 50%